2015
DOI: 10.1007/82_2015_460
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding Transcriptional Landscape in Human Aging

Abstract: Aging is a universal phenomenon in metazoans, characterized by a general decline of the organism physiology associated with an increased risk of mortality and morbidity. Aging of an organism correlates with a decline in function of its cells, as shown for muscle, immune, and neuronal cells. As the DNA content of most cells within an organism remains largely identical throughout the life span, age-associated transcriptional changes must be achieved by epigenetic mechanisms. However, how aging may impact on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…Aging is a complex physiological process with a progressive decline of adaptation and functional capacities in multiple organs of the body. The expression of many lncRNAs is affected during different types of senescence, and many lncRNAs govern the major senescent pathways such as p53/p21, pRB/p16, as well as the senescence-associated secretory phenotype (Abdelmohsen and Gorospe, 2015;Costa et al, 2016;Grammatikakis et al, 2014;Kim et al, 2016;Montes and Lund, 2016). This subsequently alters the status of aging in essential metabolic organs such as the heart and nervous system (Devaux et al, 2015;Greco et al, 2015;Szafranski et al, 2015).…”
Section: Lncrnas and Agingmentioning
confidence: 99%
“…Aging is a complex physiological process with a progressive decline of adaptation and functional capacities in multiple organs of the body. The expression of many lncRNAs is affected during different types of senescence, and many lncRNAs govern the major senescent pathways such as p53/p21, pRB/p16, as well as the senescence-associated secretory phenotype (Abdelmohsen and Gorospe, 2015;Costa et al, 2016;Grammatikakis et al, 2014;Kim et al, 2016;Montes and Lund, 2016). This subsequently alters the status of aging in essential metabolic organs such as the heart and nervous system (Devaux et al, 2015;Greco et al, 2015;Szafranski et al, 2015).…”
Section: Lncrnas and Agingmentioning
confidence: 99%
“…Beside the most famous RNA subtypes, such as coding messenger RNAs (mRNAs), transfer RNAs (tRNAs) and ribosomal RNAs (rRNAs), recent research has taken a particular interest in pseudo-genes ( -genes), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) [ 6 ]. The non-coding elements have been shown to represent one of the largest portions of transcribed molecules [ 12 , 13 , 14 , 15 ], and to be involved in a very broad set of biological processes [ 16 , 17 , 18 , 19 ], cell-fate programming [ 20 ], aging [ 21 , 22 ] and diseases [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that NONRATT013819.2- Lox co-expression and possible interaction might promote HSC transformation and proliferation by activating signaling pathways associated with ECM remodeling. However, the function of lncRNA in liver fibrosis and related mechanisms remains to be confirmed, given that a single lncRNA might potentially regulate the expression of multiple protein-coding genes at diverse levels [36]. Therefore, additional evidence regarding the cross-talk between NONRATT013819.2 and Lox remains to be experimentally validated in our future work.…”
Section: Discussionmentioning
confidence: 99%